Revision of the Oriental and East Palaearctic genus Coryptilus Gibson (Hymenoptera, Chalcidoidea, Eupelmidae) - Fusu, Lucian; Kawano, Taisuke; Park, Duk-Young (Zootaxa, 2019)
The previously monotypic genus Coryptilus Gibson (Hymenoptera: Eupelmidae) is revised and two new species are described based on females: Coryptilus circalatus Fusu sp. nov. from the Oriental region and Coryptilus longicervix Kawano & Fusu sp. nov. from both the Oriental and far eastern Palaearctic regions. Coryptilus is known only from females and previously only from the Oriental region. An illustrated key to the three known species is provided.